The traveling salesman problem: a deterministic algorithm using tabu search - López, Erasmo (2014)
We implement an algorithm corresponding to the Taboo Search method, called EraDeterministic, experimenting with the basic algorithm that ex- plores the search space and incorporating the diversification as strategy to explore new regions. The algorithm is developed in the programming environment Visual Basic 6.0 and the implementation is aimed at finding close solutions to the optimum of the problem NP−complete of the Sym- metric Traveling Salesman (STS). To test the functionality, the model is compared with some instances of the Travel Salesman Problem Library (TSPLIB), some random instances and applied to three real-life situations. Finally, we present a section with comments and conclusions, that guide us on possible future developments that demonstrate the benefits and the efficiency of the implementation.